2017
DOI: 10.1136/bmjopen-2016-013398
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cardiovascular events, arrhythmia and all-cause mortality associated with clarithromycin versus alternative antibiotics prescribed for respiratory tract infections: a retrospective cohort study

Abstract: ObjectiveTo determine whether treatment with clarithromycin for respiratory tract infections was associated with an increased risk of cardiovascular (CV) events, arrhythmias or all-cause mortality compared with other antibiotics.DesignRetrospective cohort design comparing clarithromycin monotherapy for lower (LRTI) or upper respiratory tract infection (URTI) with other antibiotic monotherapies for the same indication.SettingRoutine primary care data from the UK Clinical Practice Research Datalink and inpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…No increased long-term risk of myocardial infarction associated with clarithromycin was shown across study designs. We could observe a short-term increased risk of arrhythmia in a case-crossover study (RR 2.49; 95% CI 1.09-5.69) [37] and no increased risk in four cohort studies [22,32,37,44]. For long-term arrhythmia, we observed a marginal increased risk in two case- With roxithromycin, the number of observational studies was inadequate to obtain an overall effect summary for all outcomes.…”
Section: Stratified Analyses For Each Type Of Macrolidesmentioning
confidence: 83%
See 3 more Smart Citations
“…No increased long-term risk of myocardial infarction associated with clarithromycin was shown across study designs. We could observe a short-term increased risk of arrhythmia in a case-crossover study (RR 2.49; 95% CI 1.09-5.69) [37] and no increased risk in four cohort studies [22,32,37,44]. For long-term arrhythmia, we observed a marginal increased risk in two case- With roxithromycin, the number of observational studies was inadequate to obtain an overall effect summary for all outcomes.…”
Section: Stratified Analyses For Each Type Of Macrolidesmentioning
confidence: 83%
“…The pooled estimate did not give an increased risk (OR 1.18; 95% CI 0.96-1.44). Six cohort studies or self-controlled case series analysis [15,22,33,37,44,56] reported that the pooled estimate for long-term arrhythmia was 1.10 (95% CI 0.99-1.21) with heterogeneity of 69%. However, when results from at least two studies with the same follow-up periods were combined, no increased risk could be found (data not shown).…”
Section: Arrhythmiamentioning
confidence: 99%
See 2 more Smart Citations
“…QTc altered after trimethroprim-sulfamethoxazole may be rare [53]. Two studies on non-septic patients [54,55] showed no difference in the incidence of arrhythmia between different groups of macrolides, indicating that illness severity is probably the most important factor. A recent meta-analysis found no significant potential for provoking arrhythmias in macrolides [56].…”
Section: Medicationmentioning
confidence: 99%